1978
DOI: 10.1080/10641197809379795
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical properties of deep continental margin soils

Abstract: The engineering properties of deep continental margin sediments were determined on a worldwide basis. Deep Sea Drilling Project (DSDP) core data and material were utilized from over 900 cores obtained from 89 sites, primarily on the continental margins. Cores were recovered from penetrations to 200 m in water depths averaging 3000 m. Supplementary laboratory testing on selected cores was directed toward determining index properties and shear strength properties of the sediments. The study included a literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…DSDP reports have frequently referred to mechanical behaviour of pelagic carbonates through the various stages of diagenesis (Davie, Fenske & Serocki, 1978;Demars, 1981 ;Garrison, 1981), though slope failure in recent pelagic ooze in deep ocean basins has not been documented. Calcareous pelagic oozes should resist failure because of their relatively high internal friction angle (Demarset al, 1976;Davie et al, 1978), their reduced plasticity when compared to clays, and the slow rate of deposition which allows gradual consolidation and release of pore fluids, eliminating build-up of pore pressure which may contribute to failure (Morgenstern, 1967). Nevertheless, under special circumstances, mechanical stability of calcareous oozes may be drastically reduced.…”
Section: Geotechnical Stability Of T H E Pelagic S E D I M E N T Smentioning
confidence: 99%
“…DSDP reports have frequently referred to mechanical behaviour of pelagic carbonates through the various stages of diagenesis (Davie, Fenske & Serocki, 1978;Demars, 1981 ;Garrison, 1981), though slope failure in recent pelagic ooze in deep ocean basins has not been documented. Calcareous pelagic oozes should resist failure because of their relatively high internal friction angle (Demarset al, 1976;Davie et al, 1978), their reduced plasticity when compared to clays, and the slow rate of deposition which allows gradual consolidation and release of pore fluids, eliminating build-up of pore pressure which may contribute to failure (Morgenstern, 1967). Nevertheless, under special circumstances, mechanical stability of calcareous oozes may be drastically reduced.…”
Section: Geotechnical Stability Of T H E Pelagic S E D I M E N T Smentioning
confidence: 99%
“…They suggested that low-density of the siliceous sediment layer result in gravitational instability with the overlying non-siliceous unconsolidated sediments (density inversion). However, the bulk density values presented by Davie et al (1978) relate to sediment dominated by radiolarian and diatomaceous opaline tests. These form a highly porous network providing large space for interstitial seawater, and hence a sediment with a low bulk density.…”
Section: Diverse Origins Of the Various Chert Structuresmentioning
confidence: 90%
“…As a result of these puzzling controversial affinities the petrography and geochemistry, these chert beds were intensively studied and several theories were suggested for the formation of this variety of siliceous lithologies and structures. Davie et al (1978;in Fink and Reches, 1983a, p. 268) examined the geotechnical properties of unconsolidated marine sediments in DSDP cores and found that siliceous sediments have more than twice the water content and hence lower bulk density (1.35 g/cm 3 ) than calcareous (1.60 g/cm 3 ) and clayey (1.54 g/cm 3 ) sediments. Fink and Reches (1983a) applied these bulk density figures to the initial Mishash Formation sediments.…”
Section: Diverse Origins Of the Various Chert Structuresmentioning
confidence: 96%
“…At all burial depths, the liquid limit is appreciably higher than the water content, which is reflected in the unusually Davie et al (1978).…”
Section: Acknowledgmentsmentioning
confidence: 91%
“…ically organic sediments below. Figure 2, adapted from Deep Sea Drilling Project Technical Report 9 (1976) by Davie et al (1978), also shows numerous other data. The clay from Site 302, which has similar properties to the data presented in this paper, is from the Sea of Japan (Leg 31).…”
Section: Acknowledgmentsmentioning
confidence: 98%